PEDAGOGICAL STRATEGIES FOR TEACHING ENGLISH TO NON-LINGUISTIC UNIVERSITY STUDENTS: A LEARNER-CENTERED APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Teaching English to non-linguistic university students presents specific pedagogical challenges, including low motivation, mixed ability levels, and limited classroom time. This article explores learner-centered pedagogical strategies that enhance engagement, communicative competence, and practical language use. The paper emphasizes the importance of task-based learning, content-based instruction, collaboration, and authentic materials. It argues that effective pedagogy should connect language learning with students’ academic and professional needs.